Evaluation of Company Bankruptcy Level Using the Altman Z-Score Model: A Literature Review in Various Industrial Sectors - Ndruru, Febriani; Pinem, Clara Syntia Bella; Simamora, Mawar Geby; Simangunsong, Siti Hara; Siallagan, Hamonangan (CV Putra Publisher, 2026)
This research aims to evaluate the application of the Altman Z-Score model in assessing potential corporate bankruptcy across various industrial sectors in Indonesia and to assess its effectiveness as an early warning system. The research method employed is a literature review, examining 14 prior studies covering sectors such as manufacturing, food and beverages, pharmaceuticals, textiles, automotive, construction, banking, and insurance. The results indicate variations in bankruptcy risk levels between sectors, influenced by differences in financial characteristics, capital structure, and leverage levels. The manufacturing and food-beverage sectors tend to be more stable, while the construction and textile sectors show a higher vulnerability to distress conditions. The majority of companies in Indonesia are identified as being in the grey zone, confirming that the Altman Z-Score functions effectively as an early warning indicator rather than an absolute bankruptcy determinant. This model has proven accurate for manufacturing and non-financial sectors, but requires modification or alternative models when applied to the financial sector due to differences in financial statement structures.